2018
DOI: 10.1016/j.celrep.2018.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Mitoregulin: A lncRNA-Encoded Microprotein that Supports Mitochondrial Supercomplexes and Respiratory Efficiency

Abstract: Mitochondria are composed of many small proteins that control protein synthesis, complex assembly, metabolism, and ion and reactive oxygen species (ROS) handling. We show that a skeletal muscle- and heart-enriched long non-coding RNA, LINC00116, encodes a highly conserved 56-amino-acid microprotein that we named mitoregulin (Mtln). Mtln localizes to the inner mitochondrial membrane, where it binds cardiolipin and influences protein complex assembly. In cultured cells, Mtln overexpression increases mitochondria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
205
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(241 citation statements)
references
References 55 publications
5
205
1
1
Order By: Relevance
“…These nORFs are pervasive throughout the genome and are observed in both the coding and non coding regions 1,7 . They are variously classified as small ORFs (sORFs) 8,9 which are 1-100 amino acids in length, altORFs 10 , which are proteins in alternate frames to known proteins, Denovogenes 11 or Orphan genes 12 , Pseudogenes 1,13 , and many ncRNAs have been shown to have coding potential [14][15][16][17][18] . These new discoveries challenge traditionally held conservative definitions of ORF, as used until the recent past 19 .…”
mentioning
confidence: 99%
“…These nORFs are pervasive throughout the genome and are observed in both the coding and non coding regions 1,7 . They are variously classified as small ORFs (sORFs) 8,9 which are 1-100 amino acids in length, altORFs 10 , which are proteins in alternate frames to known proteins, Denovogenes 11 or Orphan genes 12 , Pseudogenes 1,13 , and many ncRNAs have been shown to have coding potential [14][15][16][17][18] . These new discoveries challenge traditionally held conservative definitions of ORF, as used until the recent past 19 .…”
mentioning
confidence: 99%
“…More such investigations conducted in the recent past have indicated a diverse range of functions for sORFs. These include muscle regeneration [22,23] , phagocytosis [24] , DNA replication [25] , cancer [26] and metabolism [27,28] . Despite these examples, the vast majority of novel ORF products have not been investigated rigorously and systematically because most of the past studies have focussed on only sORFs, which encode peptides that are smaller than 100 amino acids, that have been dismissed as functionally inconsequential.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have discovered that a few lncRNAs harbor small open reading frames (sORFs) that encode sORF-encoded peptides (SEPs) or micropeptides [12][13][14][15][16][17][18][19][20] . We hypothesized that there are additional transcripts currently annotated as lncRNAs that may encode micropeptides.…”
Section: An Incrna Tunar Encodes a Conserved 48-amino-acid Micropepmentioning
confidence: 99%
“…This filtering strategy dramatically reduces the likelihood of false-positive detection, but may also result in some genes that contain small open reading frames (sORFs) being mis-annotated as lncRNAs 11 . Indeed, recent studies have revealed that some of IncRNAs do contain sORFs that encode micropeptides (or microprotein, protein less than 100 amino acids in length) [12][13][14][15][16][17][18][19][20] . Micropeptides can act as modulators for larger protein complexes such as the sarco/endoplasmic reticulum Ca-ATPase (SERCA).In addition, micropeptides can also function independently by serving as ligands for receptors 21 , or scaffolds for protein-protein interactions 17 .…”
mentioning
confidence: 99%